Dampak penggunaan mirin beralkohol dalam perspektif Hukum Ekonomi Syariah - Wahyudi, Adi (Maliki Interdisciplinary Journal, 2026)
Mirin is a traditional Japanese cooking spice containing alcohol derived from fermented rice. The presence of mirin in Indonesia has sparked controversy, particularly among Muslim consumers, due to the issue of its halal status and potential health impacts. This article examines the impact of the use of alcoholic mirin from the perspective of Islamic Economic Law. The research method is a literature study with normative and descriptive analysis. The results show that although the alcohol content in mirin is relatively low, ranging from 10-14%, its use still has serious implications. From a legal perspective, the distribution of alcoholic products is strictly regulated by the Minister of Trade's regulations and the Food Law, so mirin is included in the category that must be monitored. Meanwhile, from an Islamic perspective, alcoholic mirin is categorized as doubtful or even haram due to its status as a fermented beverage. The conclusion of this article emphasizes the need for regulatory oversight, increased halal literacy, and alternative products such as non-alcoholic mirin in Indonesia.